Ménétrier disease manifested by polyposis and involved in both the small bowel and entire colon: A Case Report. Issue 36 (September 2016) - Ding, Qiang; Lu, Panpan; Ding, Shuping; Fan, Yuhui; Yan, Wei; Wang, Ying; Tian, Dean; Xia, Yujia; Liu, Mei
Abstract: Introduction: Ménétrier disease (MD) is rare that is involved in both the small bowel and entire colon. The main symptoms and the important clinical findings: We describe a case of a 76-year-old male patient whose clinical presentations include intermittent diarrhea, epigastric pain, nausea, vomiting, asitia, and weight loss. An endoscopy was performed showing a large number of irregular forms and different sizes of polypoid lesions in the gastrointestinal tract, which is rare for MD. The main diagnoses, therapeutics interventions, and outcomes: Herein, this case was diagnosed as MD, mainly dependent on endoscopic evaluation, typical clinical symptoms, and histopathological examination of biopsy. As this patient was also infected with Helicobacter pylori, the eradication of H pylori was administered. Meanwhile, a high-protein diet was enjoined, the aforementioned patient's symptoms were alleviated evidently after 1 month. Conclusion: Although the etiology of MD remained undetermined, we showed that eradication of H pylori in this case might contribute to the disease remission. This study enlarged the present understanding of MD.